Correlation of magnetic properties with deformation in electrical steels. Issue 1 (January 2016) - Papadopoulou, S
Abstract: This paper investigates the utilization of magnetic Barkhausen Noise (MBN) and hysteresis loops methods for the non-destructive characterization of deformed electrical steel samples. For this reason electrical steel samples were subjected to uniaxial tensile tests on elastic and plastic region of deformations. Both the MBN and hysteresis loops were measured. The results shown a strong degradation of the magnetic properties on plastically strains. This was attributed to the irreversible movement of the magnetic domain walls, due to the presence of high dislocation density. The resulting magnetic properties were further evaluated by examining the microstructure of the deformed samples by using scanning electron microscopy.